1999
DOI: 10.1159/000026597
|View full text |Cite
|
Sign up to set email alerts
|

No Changes in Paired Viral Antibody Titers during the Course of Acute Schizophrenia

Abstract: Although there have been many studies surveying the prevalence of specific viral antibodies in a large cohort of patients with schizophrenia, changes in antibody levels during the course of acute illness have not been fully investigated. We conducted a preliminary study investigating levels of antibodies to 5 herpesviruses (herpes simplex virus type 1, cytomegalovirus, Epstein-Barr virus, varicella-zoster virus and human herpesvirus type 6) and 6 other viruses (measles, rubella, mumps, influenza A and B and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Although numerous research reports, including our pilot study, found an association between T. gondii and schizophrenia (Mortensen et al, 2007;Torrey et al, 2007;Niebuhr et al, 2008a;Pedersen et al, 2011;Wang et al, 2013), a few others lack positive findings (Buka et al, 2001;Conejero-Goldberg et al, 2003;Leweke et al, 2004;Xiao et al, 2009;Yolken et al, 2011). Similar inconsistency is observed with other agents under consideration (Albrecht et al, 1980;Shrikhande et al, 1985;Gordon et al, 1996;Fukuda et al, 1999;Niebuhr et al, 2008b;Dickerson et al, 2010aDickerson et al, , 2010bNiebuhr et al, 2011;Jin et al, 2012).…”
Section: Discussionsupporting
confidence: 63%
“…Although numerous research reports, including our pilot study, found an association between T. gondii and schizophrenia (Mortensen et al, 2007;Torrey et al, 2007;Niebuhr et al, 2008a;Pedersen et al, 2011;Wang et al, 2013), a few others lack positive findings (Buka et al, 2001;Conejero-Goldberg et al, 2003;Leweke et al, 2004;Xiao et al, 2009;Yolken et al, 2011). Similar inconsistency is observed with other agents under consideration (Albrecht et al, 1980;Shrikhande et al, 1985;Gordon et al, 1996;Fukuda et al, 1999;Niebuhr et al, 2008b;Dickerson et al, 2010aDickerson et al, , 2010bNiebuhr et al, 2011;Jin et al, 2012).…”
Section: Discussionsupporting
confidence: 63%
“…Cytomegalovirus is a ubiquitous virus, with a very high prevalence, especially in low socio-economic populations (Cannon and Davis, 2005); therefore, it is not unusual to find significant differences between healthy controls and patients (Albrecht et al, 1980;Rimon et al, 1986;Fukuda et al, 1999;Brown et al, 2006). It is one of the main viruses involved in the appearance of brain lesions in foetuses and newly born children (Malm and Engman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The studies that stood out the most, due to their weight, were those by Brown et al (2006) and Albrecht et al (1980), representing 26.58% and 22.11% of the total sample. Additionally, the highest quality was found on the following studies: Brown et al (2006), Fukuda et al (1999 and Taller et al (1996). After combining all fifteen studies no significant overall association between infections by CMV and schizophrenia (p = 0.544) was found (OR = 0.86; CI 95%: 0.54-1.38).…”
Section: Herpesviridae Familymentioning
confidence: 99%
“…Finally, only three studies comparing infection by HHV-6 were included, all of them of acceptable quality (see Table 2 ). 22 , 24 , 28 The statistical analysis could not confirm the existence of a significant association between infection by this virus and schizophrenia (OR =0.34; 95% CI =0.49–2.42; P =0.283). Our results about IgG, IgA, and specific DNA measures are detailed in Table 3 .…”
Section: Resultsmentioning
confidence: 84%